Peningkatan Kinerja Koperasi dan UKM Melalui Kemitraan Usaha - Yunus, Muh. (ULUL ALBAB Jurnal Studi Islam, 2003)
Since economically Indonesia declined because of monetary crisis in 1997, "partnership" program considered as the alternative to solve economic problem of Cooperatives and Small and Medium Enterprises (SMEs). Its importance to decrease costs and improve production quality, to avoid supply/demand fluctuation, to create external scale of economies, to avoid uncertainty and to guaranty of good and service flow by continuously. The partnership program can be efficient, when there is no unbalance relationship conditions among Cooperatives/SMEs with their partner: Cooperatives/SMEs in "worse of" conditions and partners in "better of" condition. So, the performance Of Cooperatives/SMEs can be improved. So far, the measurement of cooperative performance focusing on finance aspect. The firm reaches high Roi considered as successfull business. Whereas, measuring business performance only on financial aspect can be bias. Therefore, it is important to have new approach on measurement business performance using "Balanced Scorecard".